Mathematical simulation of the Vertical solar still (VSS) production with the external reflector - Mohammed, Ahmed J. (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this work, a vertical solar still was constructed in Basra city in Iraq. An experimental achievement was carried out on two solar stills under the same conditions. Also, each still has one evaporative side. The still contains a basin with the total area of (0.125 m2). The still basin covers with a piece of black cotton cloth wet with brackish water. In addition, one of the still was provided with an external reflector, in order to reflect the direct sunlight to the absorber surface. The solar still was prepared from available local materials. We found in this experimental study that the efficiency without any improvement vertical solar still is (17.6 %) and increases to (38.2 %) by using vertical solar still with external reflector of the day 17 July 2012.
Keywords: Desalination; Saline Water; fresh Wate,r Solar Still; Vertical Solar Still; external reflector